Pengaruh Viral Marketing Kualitas Produk Harga Terhadap Minat Beli Produk Erigo Studi Kasus Mahasiswa Manajemen FEB Universitas Islam Malang - Zikli Seban; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted to determine the effect of Viral Marketing, Product Quality, and Price on Buying Interest in Erigo Products. Case Study of Management Students at the Islamic University of Malang Batch 2018. This research is a type of quantitative research using descriptive methods to describe existing phenomena. The population in this study is Management students of the Islamic University of Malang who purchase Erigo Products. From this population, samples will be determined using the formula from slovin so that a sample of 85 samples of data analysis in this study consists of instrument testing, classical assumption test, multiple regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the t test there is a partial influence between the viral marketing variables, product quality, price on buying interest adjusted by R Square in this study of (83.8%), the dependent variable, namely buying interest, can be explained. a n by variables Viral Marketing (X1), Product Quality (X2) and Price (X3 While 16.2%. explained by other variables outside the research model Keywords : Buying Interest, Viral Marketing, Product Quality, Price